2010
DOI: 10.1016/j.ejc.2010.05.014
|View full text |Cite
|
Sign up to set email alerts
|

A bijection between dominant Shi regions and core partitions

Abstract: It is well-known that Catalan numbers C n = 1 n+1 2n n count the number of dominant regions in the Shi arrangement of type A, and that they also count partitions which are both n-cores as well as (n + 1)-cores. These concepts have natural extensions, which we call here the m-Catalan numbers and m-Shi arrangement. In this paper, we construct a bijection between dominant regions of the m-Shi arrangement and partitions which are both n-cores as well as (mn + 1)-cores. The bijection is natural in the sense that it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 18 publications
0
30
0
Order By: Relevance
“…This question has been answered affirmatively by Vandehey in an unpublished thesis [10]; in the present paper we give a simpler proof. Another avenue is pursued by Fishel and Vazirani [3], who examine (s, t)-cores in connection with alcove geometry in the cases where t ≡ ±1 (mod s), exhibiting natural bijections between (s, t)-cores and (bounded) regions in the extended Shi arrangement.…”
Section: Introductionmentioning
confidence: 99%
“…This question has been answered affirmatively by Vandehey in an unpublished thesis [10]; in the present paper we give a simpler proof. Another avenue is pursued by Fishel and Vazirani [3], who examine (s, t)-cores in connection with alcove geometry in the cases where t ≡ ±1 (mod s), exhibiting natural bijections between (s, t)-cores and (bounded) regions in the extended Shi arrangement.…”
Section: Introductionmentioning
confidence: 99%
“…However, his discovery that the inverses of the minimal permutations correspond to a simplex is worth the price of admission. The minimal alcoves have been useful in other enumeration; see [Ath05,FV10], for example. For another example, Hohlweg, Nadeau, and Williams, in [HNW16], generalize the Shi arrangement to any Coxeter group (and beyond!)…”
Section: Enumerationmentioning
confidence: 99%
“…We mention that Fishel and Vazirani mapped partitions which are both n and nm + 1 cores to dominant regions in the m-Shi arrangment of type A n−1 in [FV10] using abacus diagrams and the root lattice. ∅ FIGURE 4.6.…”
Section: Enumerationmentioning
confidence: 99%
“…Simultaneous cores have numerous applications in algebraic combinatorics. For instance, Susanna Fishel and Monica Vazirani [FV09,FV10] showed that when t = ds ± 1 for some d ∈ N, they are naturally in bijection with certain regions of the d-Shi arrangement in type A. Drew Armstrong, Christopher Hanusa, and Brant Jones [AHJ14] extended this work to type C and related simultaneous cores to rational Catalan combinatorics.…”
Section: Introductionmentioning
confidence: 99%